The Psychological Birth of a Psychotherapist: What Are the Parallels, if Any, Between Becoming a Mother and Becoming a Psychotherapist? - Clarke, Victoria (Auckland University of Technology, 2010)
This study explores both the psychological process of becoming a mother and the psychological process of becoming a psychotherapist, and considers any parallels that may exist between the two processes. A modified systematic literature review was employed due to the appropriateness of qualitative research for the study. Findings revealed that becoming a mother and becoming a psychotherapist are both continuous, life-long developmental processes that occur for the mother, primarily within her evolving relationship with her child, and for the psychotherapist, primarily in his/her journey of self-awareness and relationship with clients. Identification, which is considered a key aspect in the acquisition of gaining an identity for the respective roles, is not always acquired immediately after the birth of a child for a mother, or after graduation for a psychotherapist, but may occur several years after these events. The study is relevant to psychotherapists and other professionals working with children, families and parent-child dyads, in understanding the mother’s psychological experience in mothering her child and how this may be played out. Additionally, the study is relevant to the new mother who may question or doubt her developing identity.
Keywords: Psychotherapy; Mother; Child psychotherapy; Becoming a mother; Becoming a psychotherapist; Mother identity; Psychotherapist identity; Mother development; Psychotherapist development